Las dictaduras militares en América del Sur y la doctrina de seguridad nacional en los años 1960 a 1980 - GALINDO, Eliseo Moreno (2016)
In this research we analyze the political, social and economic history of Brazil, Argentina, Chile and Uruguay, before and during the military dictatorship in those countries in the 1960s and 1970s examine, preferentially: 1) the different political situations in those four countries in South America before and during the coups led by the Armed Forces, with support from civil sectors and the government of the United States; 2) use as an instrument of the directives of the National Security Doctrine before and during the civil-military dictatorships in Brazil, Argentina, Chile and Uruguay; 3) changes in political institutions and economic activities and social life implemented by military governments. Through a series of phenomena that we insert in cutting of historical time we call History of the Present Time, also discussed in this investigation different theoretical, conceptual, and historiographical contributions relevant to conduct the comparative study of dictatorships in Latin South and processes of political transition. The main sources that feed the historiographical research are materials that focus the story of these four countries over the past 50 years, without excluding newspaper sources (newspapers and magazines) and official documents.